A look at the health care network: organization and challenges of the Network of Care for Persons with Disabilities (Research, Society and Development, 2021)
This study aimed to present, discuss and reflect on the formation of the Network of Care for Persons with Disabilities (RCPD) and its challenges. An Integrative Review was carried out, selecting articles published in the LILACS, SciELO, Pub Med and Google Books databases. 11 publications from public institutions and 25 articles were included in the final sample. The data were analyzed and systematized in 3 segments: The Health Care Network: constitutive and organizational elements; The RCPD and the proposals for action, challenges and weaknesses. Factors such as the permanent training of health professionals, the integration with Higher Education Institutions and the organization of services are necessary so that through the subjectivity of the humanized embracement the transformation of actions into impacting factors in the daily life and in the production of the health process of these individuals occurs. In spite of the advances assured by the legislation, the daily life of the health services does not reflect these rights yet. The fragmentation of the network of assistance to patients with disabilities has not provided the expected resolute and equitable assistance, either because of the lack of training of the health team, or the low management power of the services and even the low funding provided for this area. It is evident the need to expand and qualify the access to health care for this vulnerable population, based on the resoluteness implemented in the assistance network.